Impacts of habitat on butterfly dispersal in tropical forests, parks and grassland patches embedded in an urban landscape. (15th April 2020) - Jain, Anuj; Chan, Simon Kee Mun; Vlasanek, Petr; Webb, Edward L.
Abstract: Dispersal distances of 17 species of butterflies in tropical Singapore were significantly greater in forest than in urban habitat. Butterflies in urban plots frequently moved within suitable habitat (park/grassland) patches but rarely crossed non‐habitat patches suggesting potential isolation and a need for urban corridors.